A novel technique to incorporate the sacrotuberous ligament in perineal herniorrhaphy in 47 dogs. Issue 5 (22nd January 2021) - Cinti, Filippo; Rossanese, Matteo; Pisani, Guido
Abstract: Objective: To describe the technique and outcomes after placement of sutures around the sacrotuberous ligament during perineal hernia (PH) repair in dogs. Study design: Retrospective single‐center study. Animals: Dogs (n = 47) with PH. Methods: Medical records of dogs treated for PH between 2002 and 2020 were reviewed. Dogs were included when sutures had been placed around the sacrotuberous ligament. Short‐term outcomes and intraoperative and postoperative complications were recorded. Long‐term outcome was assessed with a questionnaire completed by owners. Results: Twenty‐eight of 47 dogs were medium or large breeds. The primary clinical sign was tenesmus in 43 dogs and dysuria‐stranguria in four dogs. Bilateral hernias were detected in 17 dogs. No intraoperative complications occurred. Median surgical time was 50 minutes for unilateral PH and 120 minutes for bilateral PH. Minor postoperative complications consisting of surgical wound swelling (9), wound dehiscence (4), and temporary tenesmus (2) occurred in 10 dogs. No major complications or recurrence were reported. The only factors associated with an increased risk of complications included increasing age ( P = .019) and surgical treatment of a recurrent PH ( P = .043). Owners consistently reported good long‐term outcomes. Conclusion: The PH repair described in this study resulted in good long‐term outcomes without major complications. Clinical significance: Placement of sutures around the sacrotuberous ligament represents an alternative during PH, but anatomical knowledge of the sciatic nerve and caudal gluteal vessels is required.